Organometallic [Fe3O(OOCC6H5)6(H2O)3](NO3) as intercalant of bentonite - Hasja Paluta Utami; Donny Marihot Siburian (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2016)
Intercalation of organometalic compounds [Fe3O(OOCC6H5)6(H2O)](NO3)∙nH2O on bentonite by weight ratio of bentonite:organometallic (1 : 1); (1 : 2); (1 : 3); and (1 : 4) has been carried out. The intercalation bentonite was characterized using FT-IR spectrophotometer, XRD and XRF anayses. Characterization using FT-IR spectrophotometer showed higher intensity of peak wavenumber at 470.6 cm-1 for Fe3-O vibration on the ratio (1 : 3). While XRD characterization showed the shift of diffraction angle of 2θ was 5.2° and has bacal spacing of 16.8 Ǻ. In the XRF characterization, the intercalation process of organometalic compounds [Fe3O(OOCC6H5)6(H2O)](NO3)∙nH2O on bentonite was occurred optimally with percentage of metal oxide reached 71.75 %. Keywords: intercalation, bentonite, organometallic, [Fe3O(OOCC6H5)6(H2O)](NO3)∙nH2O.